Composites Based on Alternative Raw Materials at High Temperature Conditions - Melichar, Tomáš; Bydžovský, Jiří; Dufka, Amos (Budapest University of Technology and Economics, 2017)
This paper presents newly developed polymer-cement composites. The primary binder (cement) was partially substituted by use of blast-furnace slag and high-temperature fly ash. A lightweight aggregate – agloporite (grain size in range 1–2 mm) was used among other components. This porous aggregate is produced from energy by-products (fly ash). Attention was focused on the behavior of the composites when exposed to elevated temperatures (400 °C–1,000°C). The influence of several different methods of temperature decrease was assessed – slow (in furnace 1°C/min) and rapid (laboratory ambient 22°C and water bath 18°C). Specific dimensional changes were determined, including strength characteristics and bulk density.

This paper presents newly developed polymer-cement composites. The primary binder (cement) was partially substituted by use of blast-furnace slag and high-temperature fly ash. A lightweight aggregate – agloporite (grain size in range 1–2 mm) was used among other components. This porous aggregate is produced from energy by-products (fly ash). Attention was focused on the behavior of the composites when exposed to elevated temperatures (400 °C–1,000°C). The influence of several different methods of temperature decrease was assessed – slow (in furnace 1°C/min) and rapid (laboratory ambient 22°C and water bath 18°C). Specific dimensional changes were determined, including strength characteristics and bulk density.
Composites Based on Alternative Raw Materials at High Temperature Conditions
Keywords: elevated temperature; rapid cooling; polymer-cement; mortar; fly ash; blast furnace slag; agloporite; strength; density; bond; residual properties; elevated temperature; rapid cooling; polymer-cement; mortar; fly ash; blast furnace slag; agloporite; strength; density; bond; residual properties